2005
DOI: 10.1093/humrep/deh554
|View full text |Cite
|
Sign up to set email alerts
|

Detailed FISH analysis of day 5 human embryos reveals the mechanisms leading to mosaic aneuploidy

Abstract: Post-zygotic chromosome loss was the most common mechanism leading to aneuploidy mosaicism for both groups, followed by chromosome gain, with fewer examples of mitotic non-disjunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 45 publications
4
62
1
2
Order By: Relevance
“…This increased genetic variation in the organism has been suggested as a mechanism for evolutionary change (Gill et al 1995) but direct evidence for this hypothesis has been sparse. In human embryos, mosaic aneuploidy arising via nondisjunction of chromosomes during mitosis (Daphnis et al 2005) or via premature centromere division (Furukawa et al 2003) has mostly been associated with abnormal development. When based on adjusted euploid chromosome numbers, the level of aneuploidy in our study fell statistically significantly from the F 3 to the F 6 generation, but that trend toward genomic stability was not continued in the F 7 generation, and levels of aneuploidy remained overall relatively high (Figure 4).…”
Section: Somatic Mosaicism and Cytotypic Variation Is Prevalent In Eamentioning
confidence: 99%
“…This increased genetic variation in the organism has been suggested as a mechanism for evolutionary change (Gill et al 1995) but direct evidence for this hypothesis has been sparse. In human embryos, mosaic aneuploidy arising via nondisjunction of chromosomes during mitosis (Daphnis et al 2005) or via premature centromere division (Furukawa et al 2003) has mostly been associated with abnormal development. When based on adjusted euploid chromosome numbers, the level of aneuploidy in our study fell statistically significantly from the F 3 to the F 6 generation, but that trend toward genomic stability was not continued in the F 7 generation, and levels of aneuploidy remained overall relatively high (Figure 4).…”
Section: Somatic Mosaicism and Cytotypic Variation Is Prevalent In Eamentioning
confidence: 99%
“…In all cases, evidence suggests that these repair pathways are coupled to covalent-modifications of chromatin (Berardi et al, 2004;Wuebbles and Jones, 2004). Many oocytes and embryos (notably in the human) also display aneuploidy, which may be exacerbated by in vitro culture (Daphnis et al, 2005;Jakobsen et al, 2006).…”
Section: Role Of Nucleic Acid Damage In Determining Zygote Viabilitymentioning
confidence: 99%
“…Recently, Lavon et al reported derivation of euploid HESCs from aneuploid embryos; their results suggest that in vitro selection may occur in favor of euploid cells [23]. Aneuploidy and chromosomal mosaicism are often found in poor-quality embryos [24], yet all of the cell lines derived by our group from poor-quality embryos thus far display a normal karyotype. Our results indicate that the process of HESC derivation rigorously selects for normal ploidy.…”
Section: Discussionmentioning
confidence: 71%